Comparative Readiness Assessment of ISPS Code Implementation in ASEAN Ports - Wahyuni, A. A. Istri Sri; Setiawan, Ariyono; Handoko, Wisnu; Hidayati, Dewi; Abdul Hadi, Abdul Razak (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2025)
This study aims to assess and compare the level of readiness in implementing the International Ship and Port Facility Security (ISPS) Code across ASEAN ports. As maritime security remains a critical priority in global logistics and trade, understanding national compliance disparities is essential for enhancing regional port resilience. Grounded in compliance theory and regional security cooperation, this research frames ISPS implementation as both a technical and institutional readiness challenge influenced by policy enforcement, infrastructure, and human resource capacity. A comparative, multi-country approach was used involving ten ASEAN countries. Five key indicators were analyzed: number of ISPS-compliant facilities, security monitoring systems, regulatory framework, personnel readiness (SDM/RSO), and operational challenges. Quantitative methods included descriptive statistics, correlation, principal component analysis (PCA), and K-means clustering to identify readiness patterns and gaps. The analysis revealed significant heterogeneity in ISPS Code implementation. Singapore demonstrated the highest readiness level, followed by Malaysia and Indonesia, while countries such as Laos and Myanmar exhibited low compliance scores. PCA results identified one dominant readiness component explaining 78% of variance. Clustering analysis grouped ASEAN countries into three readiness tiers, providing a basis for targeted regional support and harmonization strategies. Findings underscore the urgency of coordinated capacity-building, policy alignment, and funding assistance in lower-readiness states. The proposed readiness index can guide future regional security benchmarking. This study contributes a novel regional ISPS readiness index and presents the first multivariate readiness mapping of ASEAN ports, supporting data-driven policy formulation for maritime security enhancement.